Social Entrepreneurship: The Role of Institutions - Sud, Mukesh (Journal of business ethics, 2009)
A relatively small segment of business, known as social entrepreneurship (SE), is increasingly being acknowledged as an effective source of solutions for a variety of social problems. Because society tends to view “new” solutions as “the” solution, we are concerned that SE will soon be expected to provide answers to our most pressing social ills. In this paper we call into question the ability of SE, by itself, to provide solutions on a scope necessary to address large-scale social issues. SE cannot reasonably be expected to solve social problems on a large scale for a variety of reasons. The first we label the organizational legitimacy argument. This argument leads to our second argument, the isomorphism argument. We also advance three other claims, the moral, political, and structural arguments. After making our arguments, we explore ways in which SE, in concert with other social institutions, can effectively address social ills. We also present two examples of successful ventures in which SEs partnered with governments and other institutions.